To embrace or not to embrace? new academics (NAs) or new university teachers (NUTs)’ challenges and preferences between face-to-face and online teaching - Ravhuhali, Fhatuwani; Mboweni-Pataka, Hlayisani F; Tshililo, Yolanda T.; Muthivhi, Khuliso (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
The COVID-19 pandemic has caused institutions of higher education to urgently seek appropriate methods of involving students in matters of learning and teaching. Whether by conscious decision or circumstantial necessity, the imperative to embrace and implement online instruction has proven to be a formidable challenge for some academics, Particularly those who are new to academia and are referred to as New Academics (NAs) or Newly Appointed University Educators (NUTs). Framed within the context of Glasser (1998)’s Choice Theory (CT) and Rational Choice Theory (RCT), and employing a qualitative research methodology, this paper draws upon data obtained from questionnaires focused on needs analysis (NAQs) that were distributed during the induction of new academics from 2020 to 2022. The primary aim was to comprehend the challenges and preferences faced by new academics (NAs) or new university teachers (NUTs) pertaining to student instruction. NAQs were sent to NAs/NUTs prior to the induction to understand the kind of support they need, and the NAQ responses were thematically analysed. The study’s findings reveal that NAs and NUTs faced challenges in online teaching due to inadequate resources and reduced student participation. Despite the pandemic’s push for online teaching, these NUTs still favored in-person interaction. The article’s conclusions suggest that there should be adjustments in how new academics or teachers are introduced to their roles, along with enhanced support to help them develop skills for engaging and instructing students effectively in various online settings.
Journal article published in African Perspectives of Research in Teaching & Learning (APORTAL) Vol 7 (2) (2023)
Keywords: New academics; Online teaching and learning; COVID-19 Pandemic; University teachers; Needs analysis questionnaire; Face-to-face teaching; COVID-19 Pandemic; Web-based instruction; Education, Higher -- Effect of technological innovations on